Enhancing the quality of educators for excellence in secondary education in Pariaman city: Policy analysis and quality feasibility - Handriadi, Handriadi; Rusdinal, Rusdinal; Hadiyanto, Hadiyanto (Edelweiss Applied Science and Technology, 2024)
Along with decentralization and regional autonomy, the government encourages regions to develop sensitivity as stakeholders in education development. The government must strengthen its functions in education services, including setting national education policies, standards, performance-based quality control, and fostering coordination across government levels, education units, and society. This study aims to gather data on the policy direction for education implementation and the quality of educators in Pariaman City. Programs like teacher certification and improving education qualifications aim to enhance teacher quality, competence, and prestige, contributing to the improvement of Indonesia’s education system. Teachers are encouraged to improve professionalism, teaching quality, and commitment to their profession, ensuring they feel valued and proud in their roles. As a result, there is a need for continuous program development and stakeholder support in Pariaman City, as well as in districts and municipalities, to enhance the quality of basic education, including systematic management of educators.